Анализ опасности групп экcплойтов - Поддубный, В. О. (ХНУРЕ, 2019)
When creating software , it is impossible not to make mistakes, sometimes they can be almost useless, but some can be used to attack the software or the system. An exploit is a piece of software, a chunk of data, or a sequence of commands that takes advantage of a bug or vulnerability to cause unintended or unanticipated behavior to occur on computer software, hardware. Such behavior frequently includes things like gaining control of a computer system, allowing privilege escalation, or a denial-of-service (DoS or related DDoS) attack. The aim of the work was to determine the most dangerous exploits group. The result of the work shows that at this point in time browser exploits are the most dangerous and require further study and work with them